Seeking Knowledge in the Time of Covid-19: A Review of the Prophet's Hadith - Farhan Fahrurozi; Taufik Rahman (Gunung Djati Conference Series, 2021)
This study aims to discuss the hadith about the obligation to study at all times and under any circumstances and conditions, including during the Covid-19 pandemic. The research method uses a qualitative type through library research by applying the syarah hadith method associated with the Covid-19 situation and condition. The discussion of this research includes the terminology of studying, the syarah of hadith about studying, and studying in the Covid-19 era in understanding hadith. This study concludes that the hadith emphasizes the obligation to study at all times and in any situation and condition, not least during the Covid-19 pandemic by complying with health protocols and it is an obligation for scientists to find a cure for Covid-19 infection